Cytokines in relation to autoantibodies before onset of symptoms for systemic lupus erythematosus. (June 2014) - Eriksson, C; Rantapää-Dahlqvist, S
Objectives: A number of cytokines and chemokines were analysed and related to autoantibodies in blood samples pre-dating the onset of symptoms of systemic lupus erythematosus. Methods: Thirty-five patients with systemic lupus erythematosus (American College of Rheumatology criteria) were identified as having donated blood samples, prior to symptom onset, to the Biobank of northern Sweden. Altogether, 140 age- and sex-matched controls were also identified. The concentrations of interferon-α, interleukin-4, interleukin-9, interleukin-10, interferon inducible protein-10 and monocyte chemotactic protein-1 were analysed using multiplex technology and related to autoantibodies (ANA, ENA, anti-dsDNA and anti-histone antibodies) analysed from the same blood sample. Results: The interferon-γ inducible protein-10 levels were higher in the pre-symptomatic individuals than in controls ( p < 0.05) and correlated with interferon-α ( p < 0.01). The interferon-γ inducible protein-10 and interferon-α concentrations were significantly increased in individuals positive for autoantibodies: interferon-γ inducible protein-10 for ANA; anti-SSA/Ro and anti-Jo-1 antibodies; interferon-α with anti-SSB/La antibodies. The levels of interleukin-10, interferon-γ inducible protein-10 and monocyte chemotactic protein-1 increased significantly from the pre-symptomatic individuals to after onset of systemic lupus erythematosus. Conclusions: An increased concentration of interferon-γ inducible protein-10 pre-dated the onset of systemic lupus erythematosus and was related to autoantibodies before the onset of disease. The levels of interferon-γ inducible protein-10 and interferon-α were correlated. These findings support the proposal that the interferon system is important early in the pathogenesis of systemic lupus erythematosus and autoantibody formation.